Effect of telephone counselling on the knowledge, attitude and practices of contacts of confirmed COVID-19 cases in Egypt - Randa M. Said; Ghada M. Salem (AOSIS, 2021)
Background: The coronavirus disease 2019 (COVID-19) is an emerging respiratory illness. The World Health Organization declared it a public health emergency of international concern on 30 January 2020 and called for collaborative efforts, such as contact tracing and promoting the public awareness about COVID-19, and recommended prevention and control measures. Aim: The aim of this study was to assess the effect of telephone counselling on the knowledge, attitude and practices (KAPs) of contacts of COVID-19 confirmed cases towards COVID-19 epidemiology and infection prevention and control measures. Setting: Ten areas in Sharkia Governorate, Egypt divided into six rural and four urban areas. Methods: A non-randomised controlled trial was conducted in Sharkia Governorate, Egypt, from 26 March 2020 to 12 April 2020 on 208 contacts of confirmed COVID-19 cases, divided equally into two groups: an experiment group that was exposed to telephone counselling by the researchers and a control group that was exposed to routine surveillance by local health authority. A semi-structured questionnaire was used to assess the KAP of both groups towards COVID-19 before and after intervention. Results: After intervention the percent of contacts who achieved good knowledge, positive attitudes and better practice scores in the experimental group was 91.3%, 57.8% and 71.2%, respectively, compared with 13.5%, 7.8% and 16.3%, respectively, in the control group. Male gender and working group were significantly associated with bad practice score. Furthermore, there was a statistically significant positive correlation between differences in knowledge, attitudes and practices of the experimental group before and after the intervention. Conclusion: This study proved the effectiveness of telephone counselling in improving COVID-19-related KAP scores of contacts of confirmed COVID-19 cases.